2005
DOI: 10.1227/01.neu.0000170557.13788.d2
|View full text |Cite
|
Sign up to set email alerts
|

External Rotation as a Result of Suprascapular Nerve Neurotization in Obstetric Brachial Plexus Lesions

Abstract: The restoration of a fair range of true glenohumeral external rotation after neurotization of the SSN in infants with obstetric brachial plexus lesions, whether by grafting from C5 or by nerve transfer of the accessory nerve, is disappointingly low. However, it seems that compensatory techniques contribute to effectuate a considerable range of movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 25 publications
7
66
0
2
Order By: Relevance
“…Without a goniometer, the stated number of degrees may suggest a higher precision than was obtained in reality. Especially in brachial plexus lesions, compensatory movements are frequent, and the examiner should take measures to avoid compensation 25. A consensus how to assess AROM‐d should be agreed upon.…”
Section: Discussionmentioning
confidence: 99%
“…Without a goniometer, the stated number of degrees may suggest a higher precision than was obtained in reality. Especially in brachial plexus lesions, compensatory movements are frequent, and the examiner should take measures to avoid compensation 25. A consensus how to assess AROM‐d should be agreed upon.…”
Section: Discussionmentioning
confidence: 99%
“…30 Operative management is also often recommended for those infants who lack shoulder external rotation and elbow flexion by 3 to 4 months of age. 29 Given that neurotmetic lesions or root avulsions will not spontaneously recover, work has focused on the earlier identification of such lesions by imaging as a means of improving clinical decision making. 32,35 Other work has focused on additional examination findings that suggest the poor likelihood of spontaneous recovery as a means of improving surgical stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Following the description of Kawabata and colleagues [9] of the use of the spinal accessory nerve as an ipsilateral nerve transfer to the suprascapular nerve in infants with upper brachial plexus birth injuries, its use has continued to expand. Total the scores for active abduction/forward flexion and active external rotation; from [7] a Maximum shoulder score=10; decrease score by 1 point for a contracture >20°T Several groups [1,6,8,11,14,19,20] have published variable experiences with the use of the distal SAN-to-SSN transfer as part of a primary or secondary plexus reconstruction in infants who fail to demonstrate spontaneous recovery of active shoulder external rotation following a period of observation. In a retrospective review of 86 infants, Pondaag et al [14] found similar clinical results and functional scores in infants undergoing C5-to-SSN bypass grafting (n=65) and those who received direct SANto-SSN (n=21) transfers performed at a mean of 5 months of age.…”
Section: Discussionmentioning
confidence: 99%